Analysis of the role of the merdeka Mengajar Platform in teacher self-development at SDN 7 Suwawal - Latif, Sinta Norlaela; Zumrotun, Erna; Attalina, Syailin Nichla Choirin (CAHAYA PENDIDIKAN, 2024)
Merdeka Mengajar Platform (PMM) is an application that empowers teachers at SDN 7 Suwawal, supports self-development, and maximizes students' potential. Teachers are expected to master four main competencies: pedagogical, personality, social, and professional. PMM facilitates increasing competency through independent training, references, and understanding of the Merdeka Curriculum. This research aims to analyze the role of PMM in teacher self-development at SDN 7 Suwawal, its impact on teaching performance, and the obstacles faced. The method used is qualitative with case studies, collecting data through in-depth interviews, observation, and documentation from three teachers (classes I, III, VI) in the second semester of the 2024-2025 academic year. The results of interviews and observations are strengthened by documentation of real action certificates, which show concrete results from the use of PMM in teacher self-development. Class I teachers actively access PMM and participate in discussions even though they have not yet received a certificate. Class III teachers earned one certificate, while class VI teachers earned four certificates, demonstrating commitment and perseverance. The research results show that PMM helps in independent training, increasing competence, and implementing differentiated learning. Although the main obstacle is poor signal network quality, PMM has a positive impact on teachers' teaching performance, improves the quality of learning, and supports continuous professional development. By providing access to independent training, supporting a variety of teaching methods, and offering a platform for collaboration and workshops, PMM contributes significantly to improving the quality of education at SDN 7 Suwawal.